De la salle à manger aux salons de la République. La place des réseaux féminins et masculins dans l’itinéraire de la cause contraceptive (1956-1967) - Bibia Pavard (Genre & Histoire)
This article focuses on the history of the French Family Planning Association. It questions the impact of gender on the constitution of social networks and their influence on the liberalization of birth control. Two different periods stand out. First, from the creation of the association Happy Motherhood in 1956 to the beginning of the 1960s, the legitimacy of a birth control claim was forged in a female dominated organization. A few respectable women seeked support in pre-existing women networks at the national, international and local levels. Then, from the opening of the first birth control centers to the vote of new legislation on contraception in 1967, the French Family Planning Association established itself as an organization of experts, where physicians, especially men, played an increasingly leading role. Men engaged in the Family Planning mouvement were the ones who built relations within those in power, enabling contraception to become a serious political issue.